Menjelajahi perbedaan gender dalam nilai-nilai olahraga pada remaja: Sebuah studi tentang moral, kompetensi, dan status di kalangan remaja - Rizqy, Joshua Tree; Ma'mun, Amung; Nuryadi, Nuryadi; Syarifatunnisa, Syarifatunnisa; Anira, Anira; Ma’mun, Amung (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2025)
Sports have great potential in shaping the character of teenagers, but in Indonesia, they still focus more on achievement than self-value development. As a result, moral and social values that should be instilled through sports have not been optimally utilized, especially in the face of the value crisis and the increase in juvenile delinquency. This study aims to compare the values that teenagers learn through sports and to see if these values are different for boys and girls. The method used was a quantitative approach with a comparative survey design, involving 1,564 adolescents aged 12–18 years in the Bandung area, consisting of 762 boys and 802 girls. Sampling was carried out using the convenience sampling technique. The instrument used was the Youth Sport Values Questionnaire-2 (YSVQ-2), which measures three dimensions of values: morality, competence, and status. The technical aspects of the research include the preparation of instruments, coordination with schools, direct data collection, and data supervision and checking. The results showed that the total sports score of adolescent boys was 54.5 and girls was 53.4, with a difference of 1.1 points. The significance test yielded a value of 0.10 < 0.05, showing a significant difference between men and women in interpreting sports values. This study aims to compare the values teenagers learn through sports and to see if these values differ for boys and girls.